2023
DOI: 10.7589/jwd-d-21-00158
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection of Canine Distemper Virus and Rabies Virus in Wildlife Samples Submitted for Routine Rabies Testing

Abstract: Canine distemper virus (also known as Canine morbillivirus), the etiologic agent of canine distemper, is a highly contagious pathogen causing a multisystemic infection in carnivores globally. Canine distemper may be clinically indistinguishable from rabies, and outbreaks of either disease are major concerns. In the US, both diseases are endemic and managed by parenteral vaccination in domestic animals. In wildlife, oral vaccination and trap-vaccinate-release programs are available for rabies prevention, but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…The CNS sample was also positive for Canine distemper virus (CDV) by PCR (Silva et al, 2023), with a wild-type, vaccine-unrelated strain confirmed by Sanger sequencing (GenBank Accession #OR604582), a finding already reported for wild animals (Moessner et al, 2023).…”
mentioning
confidence: 57%
“…The CNS sample was also positive for Canine distemper virus (CDV) by PCR (Silva et al, 2023), with a wild-type, vaccine-unrelated strain confirmed by Sanger sequencing (GenBank Accession #OR604582), a finding already reported for wild animals (Moessner et al, 2023).…”
mentioning
confidence: 57%